Correlation of Point Shear Wave Velocity and Kidney Function in Chronic Kidney Disease. (24th April 2018) - Grosu, Iulia; Bob, Flaviu; Sporea, Ioan; Popescu, Alina; Şirli, Roxana; Schiller, Adalbert
Abstract : Objectives: Point shear wave elastography is a quantitative ultrasound‐based imaging method used in the assessment of renal disease. Among point shear wave elastographic options, 2 techniques have been studied considerably: Virtual Touch quantification (VTQ; Siemens AG, Erlangen, Germany) and ElastPQ (EPQ; Philips Healthcare, Bothell, WA). Both rely on the tissue response to an acoustic beam generated by the ultrasound transducer. The data on renal VTQ are more extensive, whereas EPQ has been used less thus far in the assessment of the kidneys. This study aimed to evaluate the performance of EPQ in the kidney and compare it with VTQ. Methods: We studied 124 participants using EPQ: 22 with no renal disease and 102 with chronic kidney disease (CKD). Ninety‐one were studied with both the EPQ and VTQ methods. We obtained 5 valid measurements in each kidney, expressed in meters per second. Results: The mean kidney stiffness measurements ± SD obtained with EPQ in the healthy control group were as follows: right kidney, 1.23 ± 0.33 m/s; and left kidney, 1.26 ± 0.32 m/s ( P  = .6). In the patients with CKD (all stages), the mean kidney stiffness measurements obtained were significantly lower: right kidney, 1.09 ± 0.39 m/s; and left kidney, 1.04 ± 0.38 m/s ( P  = .4). We observed that, similar to VTQ, EPQ values decreased with CKD progression, based on analysis of variance results using different CKD stages. From a receiver operating characteristic curve analysis, the cutoff value for an estimated glomerular filtration rate of less than 45 mL/min was 1.24 m/s, and the value for an estimated glomerular filtration rate of less than 30 mL/min was 1.07 m/s. Conclusions: When using EPQ, the kidney shear wave velocity is decreased in patients with CKD, an observation similar to that obtained by using the VTQ method.